Validation of a measure of the Satter eating competence model with low-income females - Lohse Barbara; Krall Jodi S (BMC, 2011)
Abstract Background The purpose of this study was to evaluate the construct validity of a version of the ecSatter Inventory (ecSI), a measure of eating competence (EC), as adapted for use in a low-income (LI) population. Methods Females (n = 507), aged 18 to 45 years, living in households with a history of participating in the Supplemental Nutrition Assistance Program completed a web-based survey that included the ecSI for LI (ecSI/LI) and valid measures of cognitive and affective eating behavior, food preference and practice, and food preparation. Results Most correlations and differences between eating competent and non-eating competent categories and among EC tertiles were compatible with hypothesized relationships. ecSI/LI scores were positively related with self-reported physical activity, food acceptance, fruit and vegetable intake, and food planning/resource management. ecSI/LI scores were negatively associated with body mass index, dissatisfaction with body weight, tendency to overeat in response to external or emotional stimuli, and indices of psychosocial attributes related to disordered eating. Conclusions The ecSI/LI is a valid measure of EC for low-income females and provides a tool for researchers and educators to assess intervention outcomes and further explore the EC construct.